A New Green Prospective of Non-orthogonal Multiple Access (NOMA) for 5G; Information; Vol. 11, iss. 2 - Basnayake V. Vishaka; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Sharma V. Vishal; Sharma N. Nikhil; Muthuchidambaranathan P.; Mabed H. Hakim (2020, 2020)
Title screen